Chemical composition and biological activities of essential oil from turmeric (Curcuma longa L.) rhizomes grown in Amazonian Ecuador - Jorge A. Pino; Flor M. Fon-Fay; Julio C. Pérez; Ana S. Falco; Ivones Hernández; Idania Rodeiro; Miguel D. Fernández (Revista CENIC Ciencias Químicas, 2018)
Turmeric (Curcuma longa L.) is a rhizomatous herbaceous perennial plant widely cultivated in the tropical and subtropical regions of the world. The essential oil from rhizomes has many pharmacological activities reported. The present paper reports the chemical composition and the antioxidant and antimicrobial activities of the essential oil from rhizomes grown in the Amazonian Ecuador. The essential oil was obtained by steam distillation. Analyses of the essential oil were performed by gas chromatography with flame ionization and mass selective detectors. Eighty-eight compounds were identified in the essential oil. Oxygenated compounds were the most represented class of volatiles (63.6%), including ar-turmerone (45.5%) and α-turmerone (13.4%) as major compounds. Sesquiterpene hydrocarbons were the second class (18.0%) with α-zingiberene (5.3%) as predominant. Another major constituent was the monoterpene hydrocarbon α-phellandrene (6.3%). Antioxidant properties of the essential oil were determined by radical-scavenging capacity of the oil (DPPH) and ferric-reducing antioxidant power (FRAP) methods. The essential oil had a low antioxidant activity by both methods, while it has antimicrobial activity against gram positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Pennicilium citrinum. No antimicrobial activity was found against Escherichia coli, Salmonella Enteritidis and Aspergillus niger.